Pernikahan Usia Dini Terhadap Status Gizi Anak Balita - Dartilawati Dartilawati; Muhammad Siri Dangnga; Fitriani Umar (Sarana Ilmu Indonesia (salnesia), 2021)
The number of early marriages in Pinrang Regency is still quite high. Mothers who marry at an early age are at risk of having children with poor and short nutritional status. This study aimed to determine the effect of early marriage on the nutritional status of children under five based on BB/U and TB/U. The type of research used is observational analytic with a cross sectional study approach. The sample was some toddlers in the working area of ??the Suppa Health Center, Pinrang Regency. Sampling was done by accidental sampling method as many as 94 people. Children's nutritional status was collected by anthropometric measurements of weight and height. Data analysis used fisher exact test. The results showed that 9.6% of children under five were stunted, 8.5% were malnourished and 46.8% of mothers of children under five were married at an early age. There was no effect of early marriage on the nutritional status of children under five based on BB/U (p=0,431) and TB/U (p=0,279). It is suggested the need for education to the public about the dangers of early marriage and improvement of parenting for children under five.